Foreign trade of rubber products in India (1971-72 to 1992-93) - An exploratory analysis - Mohana Kumar S; George K T; Joseph T (Proceedings of International Symposium on Plantation Crops (Placrosym XI) Calicut, 1994: Journal of Plantation Crops V24 (Suppl), 1996; p832-839)
The intricacies of foreign trade of rubber products of India have been reviewed for a period of 22years (1971-93). The paper indicated that the foreign trade in rubber products displayed a favourable balance of trade. The structure and pattern of exports and imports needs reorientation in the context of post GATT era. There is a need for restructing of the exports giving emphasis for the latex based products. These have been discussed in the light of available data.
Keywords: Foreign trade; Rubber products